Characteristics and trends of chronic obstructive pulmonary disease deaths among residents in Chongming District， Shanghai from 2002 to 2022 - SUN Xiaolei; WU Han; SHI Aiyu; DENG Hui; XU Yan; YANG Qundi (Shanghai yufang yixue)
ObjectiveTo investigate the status, characteristics of population distribution and trends of chronic obstructive pulmonary disease (COPD) deaths among the registered residents in Chongming District, Shanghai from 2002 to 2022, and to provide a scientific basis for precise prevention and control of COPD.MethodsCOPD death data were obtained from the Shanghai Chongming District Death Surveillance System, and indicators such as crude mortality rate, standardized mortality rate, mortality rate by age group, and probability of premature death were calculated for the registered residents with COPD. Joinpoint 5.0.2 software was adopted to analyze the annual percent change (APC) and average annual percent change (AAPC), followed by an analysis of trend changes.ResultsFrom 2002 to 2022, the average annual crude mortality rate and average annual standardized mortality rate of COPD among the residents of Chongming District were 73.49/100 000 and 34.00/100 000, respectively, and both were higher in males than those in females. The crude mortality rate of COPD among the residents aged ≤69 years in Chongming District was 6.78/100 000, followed by 218.28/100 000 in the age group of ≥70 years and 1 042.77/100 000 in the age group of ≥80 years, respectively. The standardized mortality rates for the whole population (AAPC=-9.75%), males (AAPC=-9.06%) , and females (AAPC=-12.25%) all showed a downward trend (all P<0.001). In addition, there was a decreasing trend in the crude mortality rates for the residents aged ≤69 years (AAPC=-7.51%), aged ≥70 years (AAPC=-9.89%), and aged ≥80 years (AAPC=-8.85%) (all P<0.001). Furthermore, the probability of premature death of COPD decreased from 1.45% in 2002 to 0.08% in 2022.ConclusionThe mortality rate and probability of early premature death of COPD among the registered residents in Chongming District, Shanghai from 2002 to 2022 show a downward trend, and the mortality rate of declining in males is slower than that in females. The elderly with advanced age account for the highest number of deaths. Therefore, targeted intervention measures should be taken for key groups to reduce the mortality rate of COPD.